2012
DOI: 10.2527/jas.53955
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and preference studies to evaluate solvent-extracted Brassica napus or Brassica juncea canola meal fed to weaned pigs1

Abstract: Inclusion of conventional dark-seeded (Brassica napus) and novel yellow-seeded (Brassica juncea) canola meal (CM) can potentially replace soybean (Glycine max) meal (SBM) in pig diets. Our objective was to examine the preference of weaned pigs fed diets containing SBM or B. napus or B. juncea CM and to compare it against previously reported growth performance data (Exp. 1 and 2). In Exp. 1 and 2, growth performance was evaluated using 220 and 240 weaned pigs, respectively, by replacing dietary SBM with up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Canola meal is the second most commonly used protein source for animal diets in the world (Arntfield and Hickling, 2011;Parr et al, 2015), but use of canola meal in diets for pigs is limited by the greater concentration of dietary fiber and reduced AA digestibility compared with SBM (Trindade Neto et al, 2012;Liu et al, 2014). However, new varieties of canola with larger seeds than conventional canola have been developed (Landero et al, 2012;Liu et al, 2014;Sanjayan et al, 2014), and the concentration of CP in the meal from these varieties is increased and the concentration of NDF is reduced (Liu et al, 2014).…”
Section: Composition Of Ingredientsmentioning
confidence: 99%
“…Canola meal is the second most commonly used protein source for animal diets in the world (Arntfield and Hickling, 2011;Parr et al, 2015), but use of canola meal in diets for pigs is limited by the greater concentration of dietary fiber and reduced AA digestibility compared with SBM (Trindade Neto et al, 2012;Liu et al, 2014). However, new varieties of canola with larger seeds than conventional canola have been developed (Landero et al, 2012;Liu et al, 2014;Sanjayan et al, 2014), and the concentration of CP in the meal from these varieties is increased and the concentration of NDF is reduced (Liu et al, 2014).…”
Section: Composition Of Ingredientsmentioning
confidence: 99%
“…The reduced fibre content may result in a greater dietary energy value for B. juncea allowing greater inclusions in pig diets vs. B. napus (Le et al 2012). However, B. juncea generally has more than double the glucosinolate content of typically sourced B. napus (Landero et al 2012a), which may decrease feed intake of animals and negatively affect thyroid, liver, and kidney functions (Tripathi and Mishra 2007). Extrusion of canola seed prior to expeller pressing may decrease the negative effects of glucosinolates by inactivating myrosinase, the enzyme that hydrolyzes glucosinolates to harmful breakdown compounds (Huang et al 1995;Liang et al 2002).…”
mentioning
confidence: 99%
“…Gluconapin has a more bitter taste than other glucosinolates, which could lead to a dislike of the taste of diets that include B. juncea CM. In a preference study, weaned pigs preferred diets with B. napus CM over diets with B. juncea CM (Landero et al, 2012). Landero et al (2013) suggested that weaned pigs are more sensitive to glucosinolates contained in B. juncea CM than grower or finisher pigs, which could be the reason why pigs in our study showed a trend, but not a significant reduction in feed disappearance when fed B. juncea compared with B. napus CM.…”
Section: Effects Of Canola Speciesmentioning
confidence: 75%